Contribution to the study of a U-shaped Patch antenna array with cardboard substrate and cuprous oxide microstrip - Vaz, Emanuel Eduardo (2025)
An array with patch antennas on a paper substrate, duly tested, and the determination of the near electric and far magnetic fields are described.